Comparison of Malaysia-Dubai approach for the Islamic dispute resolution system in Islamic finance - Kawamura, Ai (Penerbit Universiti Kebangsaan Malaysia, 2017)
This paper aims to discuss the development of the dispute resolution system for Islamic finance by a cross-national perspective in the Islamic world. The mainstays of the Islamic financial market, nowadays, are the Gulf countries and Southeast Asia. In particular, the United Arab Emirates (UAE) and Malaysia are countries that have developed the industry since its inception. Therefore, this paper will focus on these two countries as case studies. As the market grew, disputes in the Islamic finance industry also increased and raised the question of how the jurisdiction for this new industry could be separated from that of conventional finance. There are discussions on how Islamic finance dispute cases should be dealt with. Malaysia has been working on these issues by focusing on Alternative Dispute Resolution (ADR) as the potential solution. On the other hand the UAE has established an epoch-making system, the ‘Dubai Approach’. This system has been used to settle not only disputes that were related to the financial crisis that occurred in Dubai in 2009, but also those related to Islamic finance transactions. Although the dispute resolution system for Islamic finance is in the developing stage, these two countries’ systems have unique features. Therefore, this paper will indicate the developing process for the dispute resolution system for Islamic finance.